Analysis of the Effect of Regional Financial Independence on Economic Growth and Poverty Level of Regional Communities in West Kotawaringin Regency - Neya Arafah (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2022)
This research aims to analyze ; Financial independence of West Kotawaringin Regency, the influence of regional financial independence on economic growth and rate of povertyin West Kotawaringin Regency. This research use quantitative descriptive method. This research using Secondary data that form as time series from 2009-2018. Data collection using library research method. Analyze data by using path analysis model. The results showed that The Financial Independence of West Kotawaringin Regency is still low. The level of regional financial independence directly has a positive influence on economic growth and has a negative influence on the rate of poverty. Indirectly, the level of regional financial independence has a negative influence on the rete of poverty in West Kotawaringin Regency.